Evolution of pathogen and parasite avoidance behaviours†. (4th June 2018) - Sarabian, Cecile; Curtis, Val; McMullan, Rachel
Abstract : All free-living animals are subject to intense selection pressure from parasites and pathogens resulting in behavioural adaptations that can help potential hosts to avoid falling prey to parasites. This special issue on the evolution of parasite avoidance behaviour was compiled following a Royal Society meeting in 2017. Here we have assembled contributions from a wide range of disciplines including genetics, ecology, parasitology, behavioural science, ecology, psychology and epidemiology on the disease avoidance behaviour of a wide range of species. Taking an interdisciplinary and cross-species perspective allows us to sketch out the strategies, mechanisms and consequences of parasite avoidance and to identify gaps and further questions. Parasite avoidance strategies must include avoiding parasites themselves and cues to their presence in conspecifics, heterospecifics, foods and habitat. Further, parasite avoidance behaviour can be directed at constructing parasite-retardant niches. Mechanisms of parasite avoidance behaviour are generally less well characterized, though nematodes, rodents and human studies are beginning to elucidate the genetic, hormonal and neural architecture that allows animals to recognize and respond to cues of parasite threat. While the consequences of infection are well characterized in humans, we still have much to learn about the epidemiology of parasites of other species, as well as the trade-offs that hosts make in parasite defence versus other beneficial investments like mating and foraging. Finally, in this overview we conclude that it is legitimate to use the word' disgust' to describe parasite avoidance systems, in the same way that 'fear' is used to describe animal predator avoidance systems. Understanding disgust across species offers an excellent system for investigating the strategies, mechanisms and consequences of behaviour and could be a vital contribution towards the understanding and conservation of our planet's ecosystems. This article is part of the Theo Murphy meeting issue 'Evolution of pathogen and parasite avoidance behaviours'.